CRUSTAL DEFORMATION AND THE SEISMIC CYCLE ACROSS THE KODIAK ISLANDS, ALASKA - Sauber J.; Cohen S.; Carver G.; King R. (My University, 2006)
The Kodiak Islands are located ~120 to 250 km from the Alaska-Aleutian Trench and are within the southern extent of the 1964 Prince William Sound (Mw = 9.2) earthquake rupture and aftershock zone. Here we report new campaign GPS results (1993-2001) from northeastern Kodiak and reprocessed GPS results (1993-1997) from Southwestern Kodiak. The rate and orientation of the horizontal velocities, relative to a fixed North America, range from 29.7 ± 1.7 mm/yr at N30.3°W ± 3.3°, located ~120 km from the deepest point of the trench, to 8.0 ± 1.3 mm/yr at N62.4°W ± 9.3°, located ~230 km from the trench. We evaluated alternate models of coseismic and interseismic slip to test the importance of the mechanisms that account for surface deformation rates. Near the Gulf of Alaska coastal region of Kodiak the horizontal velocity can be accounted for primarily by the viscoelastic response to plate motion and a locked main thrust zone (MTZ), downdip creep, and to a lesser extent, slip in the 1964 earthquake. Farther inland the dominant mechanisms that account for post-1964 uplift rates are time-dependent, downdip creep and a locked MTZ; for the horizontal velocity component, southwest translation of western Kodiak may be important as well. On the basis of the pre-1964 and post-1964 earthquake pattern of interseismic earthquakes, we suggest that between the occurrences of great earthquakes like the 1964 event, more moderate to large earthquakes occur in the southwestern Kodiak region than near northeastern Kodiak. Copyright 2006 by the American Geophysical Union.